A 3.2 Mb deletion on 18q12 in a patient with childhood autism and high-grade myopia - Gilling, M (2008)
Autism spectrum disorders (ASDs) are a heterogeneous group of disorders with unknown aetiology. Even though ASDs are suggested to be among the most heritable complex disorders, only a few reproducible mutations leading to susceptibility for ASD have been identified. In an attempt to identify ASD susceptibility genes through chromosome rearrangements, we investigated a female patient with childhood autism and high-grade myopia, and an apparently balanced de novo translocation, t(5;18)(q34;q12.2). Further analyses revealed a 3.2 Mb deletion encompassing 17 genes at the 18q break point and an additional deletion of 1.27 Mb containing two genes on chromosome 4q35. Q-PCR analysis of 14 of the 17 genes deleted on chromosome 18 showed that 11 of these genes were expressed in the brain, suggesting that haploinsufficiency of one or more genes may have contributed to the childhood autism phenotype of the patient. Identification of multiple genetic changes in this patient with childhood autism agrees with the most frequently suggested genetic model of ASDs as complex, polygenic disorders.